Where to from Here?: Emerging Conversations on Girls' Literature and Girlhood. Issue 1 (1st March 2020) - Sardella-Ayres, Dawn; Reese, Ashley N.
Abstract: In this article, we seek to articulate a genre theory-centered definition of girls' literature, and interrogate its subgenre, the girl's bildungsroman, as contextual, cultural sites of rhetoric regarding girls and girlhood. By exploring English-language North American girls' literature, we identify it within a framework of genre as social action, tracing the protagonists' maturation into the socially determined roles of wife and mother. We explore the ways in which the girl's bildungsroman follows a home-away-home model, but with the end result of socially acceptable community integration, rather than the boy's bildungsroman' s culmination in heroic independent identity via quests and adventures.